The Great Wall of China in Polish and Serbian Travel Writings (from the 18th to the mid-20th century) - Ewertowski, Tomasz (Vernon Press, 2018)
This is a draft version of a chapter in the book Borders and Beyond. Orient-Occident Crossings in Literature edited by Adam Bednarczyk, Magdalena Kubarek, Maciej Szatkowski, published in 2018 by Vernon Press, link: https://vernonpress.com/book/436 The topic of the paper is the image of the Great Wall of China in Polish and Serbian travel writing. This construction is recognized as a historical border of China proper, which made it also a border zone between sedentary, farming Chinese civilization and nomadic or semi-nomadic peoples from the steppes and forests. In the paper we will analyze how the Great Wall was presented by Polish and Serbian travelers, who wrote about China in the 18th, 19th and the first half of the 20th century. We will concentrate not only on narratives a physical construction, but mostly on cultural and axiological aspects of descriptions of the famous edifice. The methodology of research is based on Vladimir Gvozden’s concept of travel writing, imagology, Pratt’s idea of a contact zone, Edwards Said’s concept of creative geography and as well as on post-colonial theory.
Keywords: travel writing; China; Great Wall; travelogue; Polish travelers; Serbian travelers